Post-TB sequelae in adolescent pulmonary TB survivors - C. Cesilia; F.R. Rinawan; P. Santoso; H.M. Nataprawira (IJTLD Open)
OBJECTIVE: To compare the persistent clinical symptoms, chest X-ray (CXR), spirometry and echocardiography results in adolescent survivors of drug-susceptible (DS) and drug-resistant (DR) pulmonary TB (PTB). METHODS: This retrospective cohort study was conducted in 52 adolescent PTB survivors. We compared persistent clinical symptoms, CXR, spirometry and echocardiography in DS-TB and DR-TB survivors. χ 2 test was used to compare groups (P < 0.05 significant), logistic regression analysis was used to identify risk factors, and Many-Factor Rasch Measurement Version Facets 3.86.0 was used to assess the multi-rater agreement of CXR. RESULTS: Significant differences were found in persistent clinical symptoms (higher in DS-TB survivors), CXR, and spirometry abnormalities (higher in DR-TB survivors). The echocardiography revealed a low pulmonary hypertension probability in both groups. Adolescent PTB survivors with comorbidity have 1.5 times the risk of developing pulmonary sequelae compared to non-sequelae. CONCLUSION: Pulmonary sequelae in adolescent PTB survivors were documented in both DS and DR-TB. Monitoring after treatment completion was necessary for PTB survivors, especially in adolescents.